Material incentives for anticorruption whistleblowing in the Russian Federation: issues of legal regulation - P. A. Kabanov (Russian Journal of Economics and Law)
Objective: to improve the legal regulation of material incentives for anti-corruption whistleblowing in the Russian Federation as an effective tool for counteracting the said negative social phenomenon.Methods: the methodological basis of the research is the dialectical method of cognition and general (historical, logical, systemic) and specific (grouping, analysis, synthesis, comparison, interpretation, etc.) scientific methods based on it. Results: based on the comparative-legal study of departmental, regional and municipal regulatory legal acts regulating the issues of material stimulation of the anti-corruption whistleblowing in Russia, the author describes the state of legal regulation of the said institution for combating corruption: reasons and specifics; subjects and objects of anti-corruption incentives for whistleblowing; features of applying one-time reward for it. Based on the conducted research, it can be argued that the legal regulation of stimulating anti-corruption whistleblowing has a number of significant contradictions that need to be coordinated and eliminated. The author argues that it is necessary to develop a unified approach to such regulation, to systematize the regulatory legal acts, and when implementing a one-time material incentive for anti-corruption whistleblowing - to apply differentiated and individual approach based on proportionality principle.Scientific novelty: for the first time in Russian legal science, the institution of anti-corruption whistleblowing is described as a form of approved anti-corruption behavior and a self-contained institution for combating corruption; measures to improve its legal regulation are proposed.Practical significance: it is proposed to improve the rules governing the use of the anti-corruption whistleblowing institution in order to more effectively combat corruption in the modern Russian society.